HMGB1 in severe soft tissue infections caused by Streptococcus pyogenes - Johansson, Linda; Snäll, Johanna; Sendi, Parham; Linnér, Anna; Thulin, Pontus; Linder, Adam; Treutiger, Carl-Johan; Norrby-Teglund, Anna (Frontiers in Cellular and Infection Microbiology, 2014)
Extracellular High Mobility Group Box 1 (HMGB1) has been associated with acute and chronic inflammatory conditions. However, little is known about HMGB1 in necrotizing bacterial infections. We hypothesized that the local HMGB1 response is excessive in severe soft tissue infections (STIs), which are characterized by necrosis and hyperinflammation. To explore this, tissue biopsies were collected from patients with varying severity of Streptococcus pyogenes skin and STIs, including erysipelas, cellulitis, and necrotizing fasciitis. Tissue sections were immunostained for HMGB1, S. pyogenes, and inflammatory cell infiltrates and results quantified by acquired computerized image analysis (ACIA). HMGB1 expression increased in parallel to disease severity and was significantly higher in necrotizing fasciitis than in erysipelas (p = 0.0023). Confocal microscopy of sections co-stained for HMGB1 and cell markers revealed both extracellular and cytoplasmic HMGB1, the latter of which was found predominantly in macrophages. To further verify macrophages as main source of activation triggered HMGB1 release, human macrophages were infected with clinical S. pyogenes isolates. The results demonstrated infection triggered release of HMGB1. Dual staining's visualized HMGB1 in areas close to, but not overlapping, with neutrophils, indicating a potential chemotactic role. In vitro transmigration experiments showed a chemotactic effect of HMGB1 on neutrophils. The data furthermore provided in vivo support that HGMB1 may form immunostimulatory complexes with IL-1β. Taken together, the findings provide the first in vivo evidence that HMGB1 is abundant at the local site of severe bacterial STIs and its levels correlated to severity of infections; hence, indicating its potential value as a biomarker for tissue pathology.